Deep sequencing of dsRNAs recovered from mosaic-diseased pigeonpea reveals the presence of a novel emaravirus: pigeonpea sterility mosaic virus 2 - Elbeaino, Toufic; Digiaro, Michele; Uppala, Mangala; Sudini, Harikishan (Archives of virology, 2015)
Deep-sequencing analysis of double-stranded RNA extracted from a mosaic-diseased pigeonpea plant ( Cajanus cajan L., family Fabaceae) revealed the complete sequence of six emaravirus-like negative-sense RNA segments of 7009, 2229, 1335, 1491, 1833 and 1194 nucleotides in size. In the order from RNA1 to RNA6, these genomic RNAs contained ORFs coding for the RNA-dependent RNA polymerase (RdRp, p1 of 266 kDa), the glycoprotein precursor (GP, p2 of 74.5 kDa), the nucleocapsid (NC, p3 of 34.9 kDa), and the putative movement protein (MP, p4 of 40.7 kDa), while p5 (55 kDa) and p6 (27 kDa) had unknown functions. All RNA segments showed distant relationships to viruses of the genus Emaravirus , and in particular to pigeonpea sterility mosaic virus (PPSMV), with which they shared nucleotide sequence identity ranging from 48.5 % (RNA3) to 62.5 % (RNA1). In phylogenetic trees constructed from the sequences of the proteins encoded by RNA1, RNA2 and RNA3 (p1, p2 and p3), this new viral entity showed a consistent grouping with fig mosaic virus (FMV) and rose rosette virus (RRV), which formed a cluster of their own, clearly distinct from PPSMV-1. In experimental greenhouse trials, this novel virus was successfully transmitted to pigeonpea and French bean seedlings by the eriophyid mite Aceria cajani . Preliminary surveys conducted in the Hyderabad region (India) showed that the virus in question is widespread in pigeonpea plants affected by sterility mosaic disease (86.4 %) but is absent in symptomless plants. Based on molecular, biological and epidemiological features, this novel virus is the second emaravirus infecting pigeonpea, for which the provisional name pigeonpea sterility mosaic virus 2 (PPSMV-2) is proposed.